Divergence of expression pattern contributed to neofunctionalization of duplicated HD‐Zip I transcription factor in barley. Issue 3 (7th January 2013) - Sakuma, Shun; Pourkheirandish, Mohammad; Hensel, Goetz; Kumlehn, Jochen; Stein, Nils; Tagiri, Akemi; Yamaji, Naoki; Ma, Jian Feng; Sassa, Hidenori; Koba, Takato; Komatsuda, Takao
Summary Barley (Hordeum vulgare) spikes are developmentally switched from two‐rowed to six‐rowed by a single recessive gene, six‐rowed spike 1 (vrs1), which encodes a homeodomain‐leucine zipper I class transcription factor. Vrs1 is a paralog of HvHox2 and both were generated by duplication of an ancestral gene. HvHox2 is conserved among cereals, whereas Vrs1 acquired its current function during the evolution of barley. It was unclear whether divergence of expression pattern or protein function accounted for the functionalization of Vrs1. Here, we conducted a comparative analysis of protein functions and gene expression between HvHox2 and Vrs1 to clarify the functionalization mechanism. We revealed that the transcriptional activation activity of HvHOX2 and VRS1 was conserved. In situ hybridization analysis showed that HvHox2 is localized in vascular bundles in developing spikes, whereas Vrs1 is expressed exclusively in the pistil, lemma, palea and lodicule of lateral spikelets. The transcript abundance of Vrs1 was > 10‐fold greater than that of HvHox2 during the pistil developmental stage, suggesting that the essential function of Vrs1 is to inhibit gynoecial development. We demonstrated the quantitative function of Vrs1 using RNAi transgenic plants and Vrs1 expression variants. Expression analysis of six‐rowed spike mutants that are nonallelic to vrs1 showed that Vrs1 expression was up‐regulated by Vrs4, whereas HvHox2 expression was not. These data demonstrate that the divergence of gene expression pattern contributed to the neofunctionalization of Vrs1.